Molecular determinant of substrate binding and specificity of cytochrome P450 2J2 - Liang Xu (Nature Portfolio, 2020)
Abstract Cytochrome P450 2J2 (CYP2J2) is responsible for the epoxidation of endogenous arachidonic acid, and is involved in the metabolism of exogenous drugs. To date, no crystal structure of CYP2J2 is available, and the proposed structural basis for the substrate recognition and specificity in CYP2J2 varies with the structural models developed using different computational protocols. In this study, we developed a new structural model of CYP2J2, and explored its sensitivity to substrate binding by molecular dynamics simulations of the interactions with chemically similar fluorescent probes. Our results showed that the induced-fit binding of these probes led to the preferred active poses ready for the catalysis by CYP2J2. Divergent conformational dynamics of CYP2J2 due to the binding of each probe were observed. However, a stable hydrophobic clamp composed of residues I127, F310, A311, V380, and I487 was identified to restrict any substrate access to the active site of CYP2J2. Molecular docking of a series of compounds including amiodarone, astemizole, danazol, ebastine, ketoconazole, terfenadine, terfenadone, and arachidonic acid to CYP2J2 confirmed the role of those residues in determining substrate binding and specificity of CYP2J2. In addition to the flexibility of CYP2J2, the present work also identified other factors such as electrostatic potential in the vicinity of the active site, and substrate strain energy and property that have implications for the interpretation of CYP2J2 metabolism.